2014
DOI: 10.3389/fncel.2014.00428
|View full text |Cite|
|
Sign up to set email alerts
|

Glutamic acid decarboxylase 67 expression by a distinct population of mouse vestibular supporting cells

Abstract: The function of the enzyme glutamate decarboxylase (GAD) is to convert glutamate in γ-aminobutyric acid (GABA). Glutamate decarboxylase exists as two major isoforms, termed GAD65 and GAD67, that are usually expressed in GABA-containing neurons in the central nervous system. GAD65 has been proposed to be associated with GABA exocytosis whereas GAD67 with GABA metabolism. In the present immunofluorescence study, we have investigated the presence of the two GAD isoforms in the semicircular canal cristae of wild t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
(35 reference statements)
0
4
1
1
Order By: Relevance
“…The fact that the Gad2-IRES-Cre used in the present study drove expression preferentially in a distinct subset of type I hair cells could have important implications, but was not addressed in the present study. Although there is evidence of glutamate decarboxylase isoform GAD67 expression in vestibular SCs (Tavazzani et al, 2014), the pattern of tdT-G5 expression observed in the present study suggests embryonic transcriptional regulation of Gad2 in a subset of type I hair cells. Previous studies indicate that GAD65 has multiple transcription start sites (Skak and Michelsen, 1999), and that GABA might act as a morphogen during development (Owens and Kriegstein, 2002).…”
Section: Discussioncontrasting
confidence: 66%
“…The fact that the Gad2-IRES-Cre used in the present study drove expression preferentially in a distinct subset of type I hair cells could have important implications, but was not addressed in the present study. Although there is evidence of glutamate decarboxylase isoform GAD67 expression in vestibular SCs (Tavazzani et al, 2014), the pattern of tdT-G5 expression observed in the present study suggests embryonic transcriptional regulation of Gad2 in a subset of type I hair cells. Previous studies indicate that GAD65 has multiple transcription start sites (Skak and Michelsen, 1999), and that GABA might act as a morphogen during development (Owens and Kriegstein, 2002).…”
Section: Discussioncontrasting
confidence: 66%
“…There is evidence that glutamic acid decarboxylase (GAD) is expressed in the SCs of mammalian cristae, although the specific physiological role remains uncertain. In a GAD67 transgenic mouse, SCs expressing GAD67-GFP were located primarily in the peripheral zone (PZ) of cristae ( Tavazzani et al., 2014 ). In the PZ, afferent neurons predominantly make direct synaptic contacts with type II HCs via boutons instead of calyceal synapses with type I HCs in the central zone (CZ; Lindeman, 1969 ; Lim, 1976 ; Baird et al., 1988 ; Lysakowski and Goldberg, 1997 ; Fernández et al., 1998 , 1995 ; Desai et al., 2005a ), but it is not known what role SCs may play in synaptic transmission between HCs and afferent terminals or how GAD might be involved.…”
Section: Introductionmentioning
confidence: 99%
“…However, the efferent cell group in the brainstem cannot be labeled with anti-GABA antibodies (Perachio and Kevetter 1989). A recent study used GAD67-GFP or GAD65-GFP mice that express GFP along with the two isoforms of the enzyme glutamate decarboxylase (GAD), which transform glutamate to GABA (Tavazzani et al 2014). This study concluded that only GAD67 is expressed in vestibular end organs and only in supporting cells in the peripheral regions of the semicircular canal cristae.…”
Section: Source Of Gaba In the Vestibular Peripherymentioning
confidence: 99%
“…The results of studies on gamma amino butyric acid (GABA) in the vestibular periphery are less conclusive. In mammals, GABA has been shown in efferent fibers (Kong et al 1998a;b;Matsubara et al 1995) and a recent study has found glutamic acid decarboxylase 67 (GAD67)which is required for generation of GABAand GABA itself, in supporting cells in mice vestibular end organs (Tavazzani et al 2014). Another study in mice has found GAD2 in supporting cells and mainly hair cells in mice (Holman et al 2019).…”
Section: Introductionmentioning
confidence: 99%